Addressing homelessness among people with mental illness in Ghana: suggestions from Nsawam residents - George Ofosu Oti; Kwamina Abekah-Carter; Joyce Dede Lartey; Margaret Amenuke-Edusei; Anthony Oduro (Discover Public Health)
Abstract Homelessness among people with mental illness is on the rise in many countries, including Ghana. To curb this phenomenon, appropriate measures must be taken by the relevant authorities. This study explored the perspectives of Nsawam community residents regarding how homelessness among people with mental illness could be addressed. Using the qualitative design, data were collected through semi-structured interviews with 21 participants, including traders, mental health nurses, and teachers, among others. Data collected from the interviews were subsequently transcribed and thematically analysed. Suggestions mentioned by participants were grouped under the following themes: (a) Public education; (b) getting people with mental illness off the streets; (c) establishing additional psychiatric facilities; and (d) involving family members. The tenets of the health belief model were also briefly applied to the findings. The study concluded that by considering community members’ perspectives and beliefs regarding severity, susceptibility, barriers, benefits, and cues to action, mandated institutions could design and implement effective interventions to promote support for homeless people with mental illness.